Kesiapan Pranikah Perspektif Al-Qur’an dalam Mewujudkan Keluarga Sakinah, Mawaddah, dan Rahmah - Meilani; Sahdin Hsb (Kartika: Jurnal Studi Keislaman, 2026)
Premarital readiness is an important issue in strengthening family resilience, particularly in rural communities influenced by economic pressure, social norms, and early marriage practices. This study aims to analyze Qur’anic values related to premarital readiness and their implementation in realizing a family based on sakinah, mawaddah, and rahmah in Pulo Dogom Village, North Labuhanbatu Regency. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews with 20 young married informants, field observation, and documentation. The analysis integrated empirical findings with a contextual interpretation of Qur’anic values concerning family life. The findings show that premarital readiness is not limited to administrative preparation but also includes psychological, economic, social, and spiritual dimensions. Values such as self-control, honesty, patience, responsibility, and effective communication play a significant role in maintaining household harmony. This study implies the need to strengthen premarital guidance based on Qur’anic values in a more contextual and practical way, especially for young couples in rural areas